2009
DOI: 10.1163/156856809786618510
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved issues in stereopsis: dynamic disparity processing

Abstract: Several unresolved issues in stereopsis are discussed that are related to the visual processing of dynamic disparity information. These unresolved issues include: (1) how well does the visual system compute temporal change in disparity and what kind of computation is used; (2) what is the neurophysiological basis of such processing in humans; and (3) how is the information gleaned from such processing used for guiding human action. The resolution of these issues will likely involve an adoption of a philosophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Consistent with that suggestion, Parasuraman and his associates (2009) have shown that monitoring performance is resistant to the vigilance decrement when signals for detection include ecologically significant stimuli, such as biological motion, and Szalma and his associates (2014) have found that targets embedded in natural scenes are also resistant to the vigilance decrement. Since the extraction of depth information from stereopsis provides humans with an important everyday means by which to interact with their surroundings (Fox, 1978;Patterson, 2009b), the present experiment was conducted to determine if monitoring for stereoscopic depth changes would also be resistant to the vigilance decrement. This was indeed the case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with that suggestion, Parasuraman and his associates (2009) have shown that monitoring performance is resistant to the vigilance decrement when signals for detection include ecologically significant stimuli, such as biological motion, and Szalma and his associates (2014) have found that targets embedded in natural scenes are also resistant to the vigilance decrement. Since the extraction of depth information from stereopsis provides humans with an important everyday means by which to interact with their surroundings (Fox, 1978;Patterson, 2009b), the present experiment was conducted to determine if monitoring for stereoscopic depth changes would also be resistant to the vigilance decrement. This was indeed the case.…”
Section: Discussionmentioning
confidence: 99%
“…From an operational perspective, the use of 3-D displays has been the subject of considerable interest in the human factors community (Burks et al, 2014;Patterson, 2007Patterson, , 2009aPatterson, , 2009bPatterson & Martin, 1992). A comprehensive review by McIntire and his associates (2014) indicates that although not always the case, 3-D displays improved performance over 2-D displays in a wide variety of tasks requiring the localization, identification, or manipulation of objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Greenlee and colleagues (2015) investigated the utility of stereoscopic, 3-dimensional (3-D) stimuli within visual vigilance displays. Given the ecological and evolutionary importance of stereopsis for human survival (Fox, 1978;Patterson, 2009) and Hancock's (2013) suggestion that more ecological and naturalistic stimuli may reduce the demands of vigilance tasks, Greenlee and associates predicted that stereoscopic 3-D stimuli would attenuate the vigilance decrement, and they measured global CBFV to determine whether it too would be affected by 3-D stimuli.…”
Section: Introductionmentioning
confidence: 99%